Executive Decision Synthesis A Sociotechnical Systems Paradigm - Tang, Victor (Contributions to Management Science,, 2018)
This book provides a practice-driven, yet rigorous approach to executive management decision-making that performs well even under unpredictable conditions. It explains how executives can employ prescribed engineering design methods to arrive at robust outcomes even when faced with uncontrollable uncertainty. The book presents the paradigm and its main principles in Part I; in Part II it illustrates how to frame a decision situation and how to design the decision so that it will produce its intended behavior. In turn, Part III discusses in detail in situ case studies on executive management decisions. Lastly, Part IV summarizes the book and formulates the key lessons learned.